Analysis of Ideas: International Decisions and Their Impact on the Global Political Landscape - Hayder Zuhair Jasim; elaf nofel (Tikrit Journal For Political Science, 2025)
This study discusses international decisions and their impact on world peace within a complex geopolitical context. The foundations of decision-making are reviewed through different theories, with a focus on the role of internal and external factors in shaping these decisions. The study also addresses the impact of conflicts and wars on world peace and security. The study highlights future challenges, including the rise of nationalism, resource conflicts resulting from climate change, and cyber threats, which further complicate peacemaking efforts. It stresses the need to enhance international cooperation and develop dialogue as basic strategies for dealing with crises, with the importance of re-evaluating the role of international institutions. The study emphasizes the integration of environmental and social dimensions into international decision-making to ensure an effective response to challenges, which contributes to achieving sustainable world peace.